Clinical Outcomes of Nano Arthroscopy in the Office Setting for the Treatment of Anterior Ankle Impingement. Issue 1 (January 2022) - Colasanti, Christopher; Mercer, Nathaniel P.; Garcia, Jeremie; Stornebrink, Tobias; Kerkhoffs, Gino; Dahmen, Jari; Kennedy, John G.
Category: Ankle; Arthroscopy Introduction/Purpose: The hypothesis was that IONA would provide the patient with a unique experience of their pathology and facilitate their rapid recovery through an awareness of their own condition, and that using IONA would accelerate recovery to sports-specific activities compared to the literature using standard arthroscopic procedures. Methods: This was a retrospective cohort study investigating patients who underwent IONA for anterior ankle impingement between 2019 and 2020. Clinical outcomes were evaluated using the following methods preoperatively and at final follow-up: The Foot and Ankle Outcome Scores (FAOS) and Patient-Reported Outcomes Measurement Information System (PROMIS) Pain Interference and Pain Intensity domains. A five-point Likert scale regarding patient satisfaction was evaluated at final follow-up. Wilcoxon signed-rank test was performed to compare preoperative and postoperative outcome scores. Results: Thirty-one patients were included in this study, which included eighteen males and thirteen females with a mean age of 41.7 +- 15.5 years (range, 17-69 years) and a mean body mass index (BMI) of 27.3 +- 5.7 kg/m 2 (range, 19.37-41.5). The mean follow-up time was 12. +- 1.9 months (range, 11-15 months). There were 27 patients who participated in sports activity prior to IONA-arthroscopy procedure. Of those, 26 patients (96%) returned to their sports activities. The median time to return to sports was 3.9 weeks (range, 1.5 to 12 weeks). Patients reported an overall positive experience with a mean rating scale of 9.71 +- .8 (range, 6 to 10). Twenty-seven patients (87%) reported the highest rating (10/10) for overall positive experience and felt that seeing their procedure in real-time aided in their understanding of their underlying pathology. Lastly, twenty-nine patients (94 %) expressed willingness to undergo the same procedure again. Conclusion: The current study demonstrates that IONA treatment of anterior ankle impingement results in significant pain reduction, a low complication rate, and excellent patient-reported outcomes with high rates of return to work/sport. Additionally, IONA for anterior ankle impingement leads to high patient satisfaction with a significant willingness to undergo the same procedure again.